2021
DOI: 10.14202/vetworld.2021.1093-1101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different concentration of organic and inorganic trace minerals (zinc, selenium, and chromium) supplementation on expression of chTLR4 gene and humoral immune response in broilers

Abstract: Background and Aim: Poultry production is the fastest-growing livestock sector in developing countries. In the poultry diet, trace minerals (zinc [Zn], selenium [Se], and chromium [Cr]) are normally administered in the inorganic form which has been traditionally considered as the most cost-effective and easily available but organic forms of these trace minerals have a higher bioavailability, lower dietary inclusion and cause less environmental pollution as compared to inorganic form. This study aimed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…A combination of Zn, Se, and Cr supplementation can improve the tissues' use of glucose and boost protein synthesis, both of which improve broiler growth performance [23]. Previous studies have shown that supplementing broiler diets with trace minerals (Zn, Cr and Se) boosts performance and immunity under heat stress [24]. We sought to identify the highest concentrations of Zn-Cr combination and organic-Se (LSe, HSe) for broiler diets under heat stress based on our prior results [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of Zn, Se, and Cr supplementation can improve the tissues' use of glucose and boost protein synthesis, both of which improve broiler growth performance [23]. Previous studies have shown that supplementing broiler diets with trace minerals (Zn, Cr and Se) boosts performance and immunity under heat stress [24]. We sought to identify the highest concentrations of Zn-Cr combination and organic-Se (LSe, HSe) for broiler diets under heat stress based on our prior results [25,26].…”
Section: Introductionmentioning
confidence: 99%